Water Quality Studyat Jorong Sawah Kareh Kenagarian Balimbing Kabupaten Tanah Datar - Maulana, Alwi - (STKIP PGRI Sumbar, 2014)
The need for clean water and drinking water increased with increasingrate of population growth and increased activityin the community to meet heir needs. Then, in need ofa clean water supply that can be used by the community, not in terms of quantity but in terms of quality. This study aims tolook at the quality ofthe springs and the possibility to be developed to suppor tthe needs of water in Jorong Sawah Kareh Kenagarian Balimbing. This study aims to obtain data and information and discuss data on the quality of the spring water contained in Jorong Sawah Kareh Kenagarian Balimbing. The research is descriptive quantitative. Based on the result of the research of the physical quality(temperature, color, odor, taste and turbidity). In the first sample color and turbidity does not meet drinking water quality standards that have been set by the Minister of Health Decree No. 492 / Menkes / Per / IV / 2010. It can be viewed from the quality of the water chemistry (pH, Fe, Mg, Mn, NH3) springs on samples I, II and III at pH does not meet water quality standards that have been set by the Minister of Health Decree No. 492 / Menkes / Per / IV / 2010. And it can be viewed from the biological quality (Colli Bacteria Form) spring water, the samples II and III do not meet water quality standards that have been set by the Minister of Health Decree No. 492 / Menkes / Per / IV / 2010. Springs discharge in Jorong Sawah Kareh totaled 951,523.2 liters / day, while the community needs Jorong Sawah Kareh 56873.25 liters / day, so it can be interpreted that the spring water to meet the water needs of the community Jorong Sawah Kareh.